Does wood mulch trigger microbially mediated positive plant-soil feedback in degraded boreal forest sites? A post hoc study - Stefani, Franck; Beguin, Julien; Paré, David; Morency, Marie-Josée; Martineau, Christine; Fortin, J. André; Thiffault, Nelson; Séguin, Armand (Frontiers in Plant Science, 2023)
Reforestation of degraded lands in the boreal forest is challenging and depends on the direction and strength of the plant-soil feedback (PSF). Using a gradient in tree productivity (null, low and high) from a long-term, spatially replicated reforestation experiment of borrow pits in the boreal forest, we investigated the interplay between microbial communities and soil and tree nutrient stocks and concentrations in relation to a positive PSF induced by wood mulch amendment. Three levels of mulch amendment underlie the observed gradient in tree productivity, and plots that had been amended with a continuous layer of mulch 17 years earlier showed a positive PSF with trees up to 6 m tall, a closed canopy, and a developing humus layer. The average taxonomic and functional composition of the bacterial and fungal communities differed markedly between low- and high-productivity plots. Trees in high-productivity plots recruited a specialized soil microbiome that was more efficient at nutrient mobilization and acquisition. These plots showed increases in carbon (C), calcium (Ca), nitrogen (N), potassium (K), and phosphorus (P) stocks and as well as bacterial and fungal biomass. The soil microbiome was dominated by taxa from the fungal genus Cortinarius and the bacterial family Chitinophagaceae, and a complex microbial network with higher connectivity and more keystone species supported tree productivity in reforested plots compared to unproductive plots. Therefore, mulching of plots resulted in a microbially mediated PSF that enhances mineral weathering and non-symbiotic N fixation, and in turn helps transform unproductive plots into productive plots to ensure rapid restoration of the forest ecosystem in a harsh boreal environment.